Creating business ethical codes based on organizational values / Ahmad Reza Akhavan Sarraf, Sayeed Mohsen Allameh and Ali Pishbin - Allameh, Sayeed Mohsen; Pishbin, Ali; Allameh, Sayeed Mohsen (Faculty of Business Management, 2013)
Nowadays no one can ignore the importance of culture and morality, in as much as there is no clear-cut boundaries/limitation for them. The creation of a sound culture in an organization leads to its improvement in many other aspects, so the need to concentrate on culture and morality is increasingly becoming the matter of concern. Bearing in mind that concentration on ethical codes in an organization can cause professional moralization; this paper aims to create the ethical codes based on organizational values, and further analyse them to provide practical solutions on how to easily implement these codes.